2001
DOI: 10.1128/mcb.21.20.7078-7088.2001
|View full text |Cite
|
Sign up to set email alerts
|

A 36-Amino-Acid Region of CIITA Is an Effective Inhibitor of CBP: Novel Mechanism of Gamma Interferon-Mediated Suppression of Collagen α2(I) and Other Promoters

Abstract: The class II transactivator (CIITA) is induced by gamma interferon (IFN-␥The class II transactivator (CIITA) is a master regulator of major histocompatibility complex class II (MHC-II), Ii, and DM genes (8,9,10,55,56). CIITA was initially identified by complementation of an HLA-DR Ϫ mutant B-cell line, RJ2.2.5 (55), which was created by mutagenesis followed by negative immunoselection for MHC-II-defective cells (1). CIITA is important for the constitutive expression of MHC-II in B cells and dendritic cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 65 publications
(72 reference statements)
6
104
0
Order By: Relevance
“…Ectopic CIITA expression in Tg mice, or its absence in knockout mice, has no significant repercussions on expression of the Tap1, Yars, Eif3s2, Kpna6, Ctse, Col1a2, Ptprr, Tnfsf6 and Plxna1 genes, despite previous evidence suggesting they might be regulated by CIITA [9,10,[12][13][14]20]. Several explanations could account for this discrepancy.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Ectopic CIITA expression in Tg mice, or its absence in knockout mice, has no significant repercussions on expression of the Tap1, Yars, Eif3s2, Kpna6, Ctse, Col1a2, Ptprr, Tnfsf6 and Plxna1 genes, despite previous evidence suggesting they might be regulated by CIITA [9,10,[12][13][14]20]. Several explanations could account for this discrepancy.…”
Section: Discussionmentioning
confidence: 83%
“…This suggests that CIITA is highly dedicated to the regulation of MHC-II expression. Nevertheless, a series of reports have implicated CIITA in the regulation of a wide variety of other genes functioning within and outside the immune system [8][9][10][11][12][13][14]20]. These reports suggested that CIITA might play a pleiotropic role in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations